Youth sports and concussions: Preventing preventable brain injuries. One client, one cause, and a new law - Adler, R. H. (Physical Medicine & Rehabilitation Clinics of North America, 2011)
Effective concussion prevention and management for youth athletes requires both education and legislation. Education alone effectively begins the awareness of an issue, but does not change behavior. Education and legislation are required to prevent preventable concussion and brain injuries in youth athletes.